Twin-Arginine Translocation System in Helicobacter pylori: TatC, but Not TatB, Is Essential for Viability - Stéphane L. Benoit (American Society for Microbiology, 2014)
ABSTRACT The twin-arginine translocation (Tat) system, needed to transport folded proteins across biological membranes, has not been characterized in the gastric pathogen Helicobacter pylori. Analysis of all H. pylori genome sequences available thus far reveals the presence of single copies of tatA, tatB, and tatC needed for the synthesis of a fully functional Tat system. Based on the presence of the twin-arginine hallmark in their signal sequence, only four H. pylori proteins appear to be Tat dependent: hydrogenase (HydA), catalase-associated protein (KapA), biotin sulfoxide reductase (BisC), and the ubiquinol cytochrome oxidoreductase Rieske protein (FbcF). In the present study, targeted mutations were aimed at tatA, tatB, tatC, or queA (downstream gene control). While double homologous recombination mutations in tatB and queA were easily obtained, attempts at disrupting tatA proved unsuccessful, while deletion of tatC led to partial mutants following single homologous recombination, with cells retaining a chromosomal copy of tatC. Double homologous recombination tatC mutants were obtained only when a plasmid-borne, isopropyl-β-d-thiogalactopyranoside (IPTG)-inducible copy of tatC was introduced prior to transformation. These conditional tatC mutants could grow only in the presence of IPTG, suggesting that tatC is essential in H. pylori. tatB and tatC mutants had lower hydrogenase and catalase activities than the wild-type strain did, and the ability of tatC mutants to colonize mouse stomachs was severely affected compared to the wild type. Chromosomal complementation of tatC mutants restored hydrogenase and catalase activities to wild-type levels, and additional expression of tatC in wild-type cells resulted in elevated Tat-dependent enzyme activities. Unexpectedly, the tat strains had cell envelope defects. IMPORTANCE This work reports the first characterization of the twin-arginine translocation (Tat) system in the gastric pathogen Helicobacter pylori. While tatB mutants were easily obtained, only single-crossover partial tatC mutants or conditional tatC mutants could be generated, indicating that tatC is essential in H. pylori, a surprising finding given the fact that only four proteins are predicted to be translocated by the Tat system in this bacterium. The levels of activity of hydrogenase and catalase, two of the predicted Tat-dependent enzymes, were affected in these mutants. In addition, all tat mutants displayed cell envelope defects, and tatC mutants were deficient in mouse colonization.